Ethical Insights: A Brief Introduction - Birsch Douglas (Mc Graw Hill, 2002)
This is a brief, accessible, affordable supplement for any applied ethics course. The text covers eight ethical theories, with each chapter focusing on a key ethical insight that helps establish moral guidelines to solve ethical problems.